2006
DOI: 10.1210/jc.2006-1044
|View full text |Cite
|
Sign up to set email alerts
|

Increased Subcutaneous and Epicardial Adipose Tissue Production of Proinflammatory Cytokines in Cardiac Surgery Patients: Possible Role in Postoperative Insulin Resistance

Abstract: Both sc and epicardial adipose tissue is a source of proinflammatory cytokines in cardiac surgery patients and may contribute to the development of postoperative insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
145
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(159 citation statements)
references
References 36 publications
9
145
2
3
Order By: Relevance
“…32,33 In a recent study, the authors concluded that EAT acts as an extremely active organ that produces several bioactive adipokines, as well as proinflammatory and proatherogenic cytokines. [9][10][11][12][13] Levels of most of these proinflammatory cytokines were, in general, increased and these cytokines were found to be associated with atherosclerosis in ESRD patients. [34][35][36] In this study, we demonstrated that AIP and EAT measurements were increased in ESRD patients when compared with healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 In a recent study, the authors concluded that EAT acts as an extremely active organ that produces several bioactive adipokines, as well as proinflammatory and proatherogenic cytokines. [9][10][11][12][13] Levels of most of these proinflammatory cytokines were, in general, increased and these cytokines were found to be associated with atherosclerosis in ESRD patients. [34][35][36] In this study, we demonstrated that AIP and EAT measurements were increased in ESRD patients when compared with healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the authors demonstrated that EAT acts an extremely active organ that produces several bioactive adipokines, as well as proinflammatory and proatherogenic cytokines including tumor necrosis factor (TNF)-a, interleukin (IL)-6, resistin, visfatin, omentin, leptin, plasminogen activator inhibitor-1 (PAI-1) and angiotensinogen. [9][10][11][12][13] We recently showed that EAT is increased in HD and PD patients 14,15 and this active visceral fat tissue is closely related with malnutritioninflammation-atherosclerosis/calcification syndrome (MIAC) in this population. 16 Logarithmic ratio of triglycerides to HDL was defined as atherogenic index of plasma (AIP) and this index was found to be closely associated with atherosclerosis in general population.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a few reports on cytokines in epicardial adipose tissue. 5,[18][19][20][21][22][23] Iacobellis, et al reported that mRNA expression of adiponectin in epicardial adipose tissue was significantly lower in subjects with severe CAD than in those without CAD. 21) Our data suggest that enhanced infiltration of inflammatory cells into EAT may account for inflammatory cytokine expression in EAT of CAD patients, although our sample size was too small to draw a definitive conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Epicardial adipose tissue is metabolically active and a source of FFA and several bioactive adipokines such as adiponectin, TNF , IL-1, IL-6, neural growth factor and resistin 34,35) . Some of these factors might substantially affect cardiovascular function and morphology and, thereby, directly contribute to the development of the cardiovascular complications of increased adiposity as well as insulin resistance 34,35) .…”
Section: Epicardial Adipose Tissuementioning
confidence: 99%